Impact of electrode geometry and thickness on planar on-chip microsupercapacitors. Issue 52 (26th August 2020) - Vyas, Agin; Wang, Kejian; Li, Qi; Saleem, Amin M.; Bylund, Maria; Andersson, Rickard; Desmaris, Vincent; Smith, Anderson; Lundgren, Per; Enoksson, Peter
Abstract : We present an in-depth analysis of the impact of geometry and carbon nanofiber thickness on CMOS compatible microsupercapacitor performance. Abstract : We report an assessment of the influence of both finger geometry and vertically-oriented carbon nanofiber lengths in planar micro-supercapacitors. Increasing the finger number leads to an up-scaling in areal power densities, which increases with scan rate. Growing the nanofibers longer, however, does not lead to a proportional growth in capacitance, proposedly related to limited ion penetration of the electrode.